Factors influencing employees’ ethical behavior: Empirical study of employees in Iraqi organizations / Husam Mohammed Kamil Alhaboose - Husam Mohammed Kamil , Alhaboose (2020)
In contemporary organizations, ethics has become one of the most vital aspects of organizational sustenance in today’s competitive business world. Earlier studies have considered employees as a potential source of success for an organization. Moreover, prior studies have designated the essential role of ethical leadership in influencing employees’ ethical behavior. Therefore, this study tries to contribute to the literature by examining the direct effect of ethical leadership on employees’ ethical behavior via the two-mediating role of ethical climate and organizational justice. Most importantly, moral identity was also identified as a boundary condition on the relationship of ethical leadership, ethical climate, organizational justice, and ethical behavior of employees. Data were collected through questionnaires which were completed by 620 full-time employees working at 33 Iraqi organization from five Iraqi provinces and involved in manufacturing, retailing, medical, insurance, information technology, legal, finance, and telecommunication sectors. Structural Equation Modeling (SEM) was used to test the model and data analysis was carried out using Structural Equation Modelling–Partial Least Square (SEM-PLS) and PROCESS macro. The results showed that ethical leadership behavior has a significant relationship with ethical behavior. The study also revealed the relationship between ethical leadership and employees’ ethical behavior is positively mediated by work ethical climate and organizational justice. Moreover, the moderation role of moral identity was a significant on the relationship of ethical leadership, and employees’ ethical behavior, on the other hand, was insignificant between work ethical climate, organizational justice, and employees’ ethical behavior. The theoretical model of this study was underpinned by social exchange and social learning theory to improve the exchange relationship between managers and employees as well as to enhance employees’ ethical behavior. This study provides theoretical and practical contributions to business ethics and leadership studies.